Improving the effectiveness of performance appraisal systems in public sector administrative divisions - Nugraha, Moch Yusuf Giri; Putri, Ulfa Rahma; Ahmad, Fandi (Privietlab, 2025)
This study explores the suboptimal implementation of performance appraisals for BLUD employees in public hospitals. This research aims to identify existing issues and formulate draft guidelines to enhance the appraisal process. Using a qualitative approach, data were collected through interviews, observations, and document analysis. The analysis refers to Gary Dessler’s book “Human Resource Management” to address the lack of accurate measurement in current practices. The findings reveal several challenges, including the absence of performance dialogue, difficulties in validating performance realization data, subjective behavioral assessments, and unclear evaluation criteria. In response, this study proposes guidelines to serve as a reference for all stakeholders involved in the appraisal process. Additional recommendations include the use of shared digital storage (e.g., Google Drive) for performance documentation and the development of behavior assessment instruments based on the BARS method to improve objectivity and ease of evaluation. These efforts are expected to support a more accurate and accountable performance appraisal system